Overexpression of the Nek2 kinase in colorectal cancer correlates with beta‐catenin relocalization and shortened cancer‐specific survival. Issue 7 (16th July 2014) - Neal, Christopher P.; Fry, Andrew M.; Moreman, Catherine; McGregor, Angus; Garcea, Giuseppe; Berry, David P.; Manson, Margaret M.
<x xml:space="preserve">Abstract</x> The serine/threonine kinase Nek2 (NIMA‐related kinase 2) regulates centrosome separation and mitotic progression, with overexpression causing induction of aneuploidy in vitro. Overexpression may also enable tumour progression through effects upon Akt signalling, cell adhesion markers and the Wnt pathway. The objective of this study was to examine Nek2 protein expression in colorectal cancer (CRC). Nek2 protein expression was examined in a panel of CRC cell lines using Western blotting and immunofluorescence microscopy. Nek2 and beta‐catenin expression were examined by immunohistochemistry in a series of resected CRC, as well as their matched lymph node and liver metastases, and correlated with clinicopathological characteristics. Nek2 protein expression in all CRC lines examined was higher than in the immortalised colonocyte line HCEC. Nek2 overexpression was present in 86.4% of resected CRC and was significantly associated with advancing AJCC tumour stage and shortened cancer‐specific survival. Elevated Nek2 expression was maintained within all matched metastases from overexpressing primary tumours. Nek2 overexpression was significantly associated with lower tumour membranous beta‐catenin expression and higher cytoplasmic and nuclear beta‐catenin accumulation. These data support a role for Nek2 in CRC progression and confirm potential for Nek2 inhibition as a therapeutic avenue in CRC. J. Surg. Oncol. 2014 110:828–838. © 2014 Wiley Periodicals, Inc.